2018
DOI: 10.4081/gi.2018.7629
|View full text |Cite
|
Sign up to set email alerts
|

Risk scoring systems to predict in-hospital mortality in patients with acute variceal bleeding due to HCV-induced liver cirrhosis

Abstract: This study was designed to validate and to compare accuracy of the prognostic scores; mainly Child Turcotte Pugh (CTP), creatinine-modified Child Turcotte Pugh (CTP-Cr), model for end-stage liver disease (MELD), albumin bilirubin score (ALBI), and AIMS65, for the predicting clinical outcomes in cirrhotic Egyptian patients presenting with acute variceal bleeding (AVB). Retrospective single center study involving 725 patients presenting with AVB due to liver cirrhosis and HCV infection either alone or mixed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Eleven out of 28 studies were prospective. Nine studies reported sensitivity and specificity values [ 19 , 21 , 26 , 27 , 32 , 34 , 36 , 38 , 42 ]. All studies presented AUCs and 95% CIs.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven out of 28 studies were prospective. Nine studies reported sensitivity and specificity values [ 19 , 21 , 26 , 27 , 32 , 34 , 36 , 38 , 42 ]. All studies presented AUCs and 95% CIs.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of outcomes, 44 studies reported mortality, 810,18,2030,3237,39,4143,4749,5255,58,6366,6871,7375 27 rebleeding, 8,19,20,22,25,2931,34,35,38–40,43,45,46,50,51,5557,60,68,70,72,…”
Section: Resultsmentioning
confidence: 99%
“…The rate of HI/shock ranged between 1.2% and 68.3% of the eligible studies. The source of bleeding was UGIB in 54 of the included studies, [8][9][10][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]36,37,[39][40][41][42][43][44][45][47][48][49][50][52][53][54][55][58][59][60][63][64][65][66][67][68][69][70][71][72][73][74]…”
Section: Basic Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitation of prognostic scores in variceal bleeding may be the fact that only a few of them (AIM65, ABC) are correlated to the severity of the liver failure. Some improved CPT variants including creatinine level were also proposed in order to increase accuracy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%